Dog Bite Prevention: A New Screening Tool - Dixon, Cinnamon A. (2011)
OBJECTIVES: To determine what children know about preventing dog bites and parental desires for dog bite prevention education. STUDY DESIGN: This cross-sectional study sampled 5-15 year olds and their parents/guardians presenting to a pediatric emergency department with non-urgent complaints or dog bites. Pairs completed surveys and knowledge-based simulated scenario tests developed from American Academy of Pediatrics (AAP) and Center for Disease Control and Prevention (CDC) dog bite prevention recommendations. Regression analyses modeled knowledge test scores and probability of passing; a passing score was ≥11/14 questions. RESULTS: Of 300 parent/child pairs, 43% of children failed the knowledge test. Older children had higher odds of passing the knowledge test than younger children, as did children with white parents versus non-white parents. No associations were found between knowledge scores and other sociodemographic or experiential factors. Over 70% of children had never received dog bite prevention education, although 88% of parents desired it. CONCLUSION: Dog bites are preventable injures disproportionately affecting children. Dog bite prevention knowledge in our sample was poor, particularly among younger children and children with non-white parents. Formal dog bite prevention education is warranted and welcomed by a majority of parents.